Interleukin-4 Responsive Dendritic Cells Are Dispensable to Host Resistance Against Leishmania mexicana Infection - Osero, Bernard Ong’ondo; Cele, Zama; Aruleba, Raphael Taiwo; Maine, Rebeng A.; Ozturk, Mumin; Lutz, Manfred B.; Brombacher, Frank; Hurdayal, Ramona (Frontiers in Immunology, 2022)
IL-4 and IL-13 cytokines have been associated with a non-healing phenotype in murine leishmaniasis in L. mexicana -infected BALB/c mice as demonstrated in IL-4−/−, IL-13−/− and IL-4Rα-/- global knockout miouse studies. However, it is unclear from the studies which cell-type-specific IL-4/IL-13 signaling mediates protection to L. mexicana. Previous studies have ruled out a role for IL-4-mediated protection on CD4+ T cells during L. mexicana infections. A candidate for this role may be non-lymphocyte cells, particularly DCs, as was previously shown in L. major infections, where IL-4 production drives dendritic cell-IL-12 production thereby mediating a type 1 immune response. However, it is unclear if this IL-4-instruction of type 1 immunity also occurs in CL caused by L. Mexicana, since the outcome of cutaneous leishmaniasis often depends on the infecting Leishmania species. Thus, BALB/c mice with cell-specific deletion of the IL-4Rα on CD11c+ DCs were infected with L. mexicana promastigotes in the footpad and the clinical phenotype, humoral and cellular immune responses were investigated, compared to the littermate control, IL-4Rα-/lox mice. Our results show that CL disease progression in BALB/c mice is independent of IL-4Rα signaling on DCs as CD11ccreIL-4Rα-/lox mice had similar footpad lesion progression, parasite loads, humoral responses (IgE, IgG1, IgG 2a/b), and IFN-γ cytokine secretion in comparison to littermate controls. Despite this comparable phenotype, IL-4 production in CD11ccreIL-4Rα-/lox mice was significantly increased with an increasing trend of IL-13 compared to littermate controls. Moreover, the absence of IL-4Rα signaling did not significantly alter the frequency of CD4 and CD8 lymphocytes nor their activation, or memory phenotype compared to littermate controls. However, these populations were significantly increased in CD11ccreIL-4Rα-/lox mice due to greater total cell infiltration into the lymph node. The recruitment of macrophages, DCs, neutrophils, and MoDCs into LN was comparable to littermate IL-4Rα-/lox mice. Interestingly, the similar levels of IL-12p70 and IL-10 produced by BMDCs between CD11ccreIL-4Rα-/lox mice and littermate controls highlighted unimpaired IL-4-mediated DC instruction. Nevertheless, maturation/activation and nitrite/urea production were not affected. Together, this study suggests that IL-4 Rα signaling on DCs is not key in the regulation of immune-mediated protection in mice against L. mexicana infection.